Perbandingan Prokrastinasi Akademik Berdasarkan Keaktifan Dalam Organisasi Kemahasiswaan - Alaihimi, Wan Shurna; -, Arneliwati -; -, Misrawati - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This study aims to compare the academic procrastination based on active in student organizations conducted in School of Nursing in University of Riau. The research method used descriptive analytic with comparative study. The sampling method was proportionate stratified random sampling with a total sample size of 146 students. The instrument used was a questionnaire which has the validity tested and reliability. The analysis used was univariate using frequency distribution and bivariate analysis using Chi-Square test. The results showed that students who were not active in student organizations tend to have a high level of academic procrastination compared with students who were active in student organizations and there was very significant. According results of the Chi-square test can be concluded that there are significant comparisons based on academic procrastination active in student organizations (ρ 0.000 <α 0.05). Base on the result, reseacher suggest to the students to follow the student organization because it can provide more benefits that are not found in academic and it also make the student have a better time management and have lower levels of academic procrastination in order to improve the quality of students as individuals. Keywords : academic procrastination, procrastination, student organizations